Postexercise rehydration with beer impairs fluid retention, reaction time, and balance - Flores Salamanca, Rebeca (2014)
artículo (preprint)--Universidad de Costa Rica, Centro de Investigación en Ciencias del Movimiento Humano (CIMOHU). 2014